Low-level laser therapy for pain relief after episiotomy: a double-blind randomised clinical trial - Santos, Jaqueline de O. [UNESP]; de Oliveira, Sonia M. J. V.; da Silva, Flora M. B.; Nobre, Moacyr R. C.; Osava, Ruth H.; Riesco, Maria L. G. (Wiley-Blackwell, 2012)
Aims and objectives. To evaluate the effectiveness of a low-level laser therapy for pain relief in the perineum following episiotomy during childbirth. Background. Laser irradiation is a painless and non-invasive therapy for perineal pain treatment and its effects have been investigated in several studies, with no clear conclusion on its effectiveness. Design. A double-blind randomised controlled clinical trial. Method. One hundred and fourteen women who underwent right mediolateral episiotomies during vaginal birth in an in-hospital birthing centre in São Paulo, Brazil and reported pain =3 on a numeric scale (010) were randomised into three groups of 38 women each: two experimental groups (treated with red and infrared laser) and a control group. The experimental groups were treated with laser applied at three points directly on the episiotomy after suturing in a single session between 656 hours postpartum. We used a diode laser with wavelengths of 660 nm (red laser) and 780 nm (infrared laser). The control group participants underwent all laser procedures, excluding the emission of irradiation. The participants and the pain scores evaluator were blinded to the type of intervention. The perineal pain scores were assessed at three time points: before, immediately after and 30 minutes after low-level laser therapy. Results. The comparison of perineal pain between the three groups showed no significant differences in the three evaluations (p = 0.445), indicating that the results obtained in the groups treated with low-level laser therapy were equivalent to the control group. Conclusions. Low-level laser therapy did not decrease the intensity of perineal pain reported by women who underwent right mediolateral episiotomy. Relevance to clinical practice. The effect of laser in perineal pain relief was not demonstrated in this study. The dosage may not have been sufficient to provide relief from perineal pain after episiotomy during a vaginal birth.
Keywords: episiotomy; laser therapy; lasers; low intensity; nurses; nursing; pain; perineum; postpartum period